Women's Stereotypes in Ludruk: Sexist Humor and Gender Dynamics in East Java - Rachmad, Rio Nur; Munandar, Aris (Fakultas Ilmu Budaya, Universitas Mulawarman, 2026)
This study examines sexist humor in Ludruk, a traditional theatrical comedy performance from East Java, and explores how such humor reflects and reinforces local gender dynamics. Employing a descriptive qualitative approach, the research is based on library analysis of selected Ludruk video recordings, which were transcribed and analyzed using content analysis and critical discourse analysis, guided by Sara Mills’ feminist discourse framework. The findings reveal that sexist humor, often emerging through actor interactions, serves as a discursive site where patriarchal values are reproduced, positioning women as passive and subordinate figures. Far from being merely a source of entertainment, Ludruk humor functions as a cultural mechanism that sustains gender stereotypes and legitimizes unequal power relations within East Javanese society.